Other Significant Metabolites. Myo-Inositol, GABA, Glutamine, and Lactate. - Best, J; Stagg, C; Dennis, A (Elsevier, 2013)
Advances in acquisition parameters have meant that an increased number of metabolites are readily quantified using magnetic resonance spectroscopy. Here we discuss the most commonly acquired of these: myo-inositol, γ-aminobutyric acid (GABA), glutamine, and lactate. Myo-inositol is commonly taken to be a marker of glial activity and abnormalities have been described in a number of neurodegenerative conditions. GABA, the major inhibitory neurotransmitter in the brain, can be accurately quantified using spectral editing and informs the understanding of the role of inhibitory processes in normal physiology and in the pathology of a number of neurological and psychiatric conditions. Glutamine, sometimes difficult to distinguish from glutamate, is an abundant amino acid in the central nervous system and has a number of roles within the brain, particularly in the breakdown of urea. Lactate, a byproduct of metabolism, has potential roles both as a method of quantifying the rate of metabolism in the brain and as a marker of pathological processes. © 2014 Elsevier Inc. All rights reserved.